PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MODUL DALAM MATERI TATA NAMA SENYAWA - Permatasari, Hellena Claudya; Shaputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study were to determine whether there was a significant  difference  of achievement between student who taught using make a match and conventional modelon material of chemical nomenclature and to determine effect size of make a match learning model. The form ofresearch used in thisstudywas nonequivalent control group design. All X.IPA classes of  SMAN 1 Sungai Raya were taken as research population. From that population, two classes were chosen through purposive sampling technique. Samples in this study were X.IPA 1 class as control  class and the X.IPA 5 class as exsperimental class.These classes were chosen based on their atomic structure score in which the selection of experimental class due to its linear score than control class. Achievement test, interview guidelines and observation sheet were used asa data collection. Based on U-mann whitney test, there was a significant difference of achievement between students who taught using make a match and conventional model.According to calculation using cohen formula, the effect size of make a match learning model was 1,011 which was inzone of desire effect. Keywords: Cooperative learning,  Make a match type, Chemical nomenclature